Factors Affecting Participation of Registered Nurses in Continuing Nursing Education among Selected Private Hospital in Penang, Malaysia - Yee , Bit Lian; Tan , Woei Ling; Saranyah Nachiappen; Nur Farahin Mohamed Jajali (Lincoln University College, Asia Pacific Higher Learning Sdn Bhd, 2022)
Introduction: The rapidly changing health care needs of clients, the changing roles of nurses, and rapid technological advancement make Continuous Nursing Education (CNE) necessary for nurses to maintain up-to-date nursing knowledge and skills to face the ever-increasing societal demands. Objective: The objective of this study is to identify factors that motivate and deter CNE participation among nurses. Methods: A cross-sectional descriptive study design was conducted in a selected private hospital, Penang, Malaysia. 100 respondents who fulfilled the inclusion criteria participated in this study. This study utilised a self-administered questionnaire related to factors that motivate and deter nurses’ participation in CNE. Results: The results of this study showed that both factors that motivate and hinder CNE participation among the registered nurses were above the mean of 3.0 out of 5 scores. above theAll factors that influence have mean of more than 3.0. There is no significant difference between various categories of the department on factors that influence CNE participation among registered nurses at the selected private hospital in Penang; F (6, 81) = 0.558, p = 0.763 > 0.05. Conclusion: This study indicated that there is a need to develop an effective strategy for nurses to participate in the future CNE.